2023
DOI: 10.1107/s2059798323005648
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium etli has two L-asparaginases with low sequence identity but similar structure and catalytic center

Abstract: The genome of Rhizobium etli, a nitrogen-fixing bacterial symbiont of legume plants, encodes two L-asparaginases, ReAIV and ReAV, that have no similarity to the well characterized enzymes of class 1 (bacterial type) and class 2 (plant type). It has been hypothesized that ReAIV and ReAV might belong to the same structural class 3 despite their low level of sequence identity. When the crystal structure of the inducible and thermolabile protein ReAV was solved, this hypothesis gained a stronger footing because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…It is prominently represented by two isoforms, ReAIV and ReAV, derived from Rhizobium etli , a nitrogen-fixing bacterial symbiont of the legume common bean. ReAIV is constitutive and thermostable, while ReAV is inducible and thermolabile, the denaturation temperatures being, respectively, 72°C and 51°C ( Loch et al, 2023 ). The level of sequence homology between ReAIV and ReAV is rather low, with ∼31% identity and ∼45% similarity, and both proteins have no sequence similarity to other known enzymes with this activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is prominently represented by two isoforms, ReAIV and ReAV, derived from Rhizobium etli , a nitrogen-fixing bacterial symbiont of the legume common bean. ReAIV is constitutive and thermostable, while ReAV is inducible and thermolabile, the denaturation temperatures being, respectively, 72°C and 51°C ( Loch et al, 2023 ). The level of sequence homology between ReAIV and ReAV is rather low, with ∼31% identity and ∼45% similarity, and both proteins have no sequence similarity to other known enzymes with this activity.…”
Section: Introductionmentioning
confidence: 99%
“…The level of sequence homology between ReAIV and ReAV is rather low, with ∼31% identity and ∼45% similarity, and both proteins have no sequence similarity to other known enzymes with this activity. Despite their sequence differences, the two isoforms show high structural similarity, with the caveat that the longer ReAV sequence (367 vs. 335 residues) has additional structural elements (such as longer loops) that make it a less compact protein ( Loch et al, 2023 ) ( Figure 1A ). The crystal structures of both enzymes revealed that their unusual active site contains a highly specific Zn 2+ binding site, formed by a Lys and two Cys residues ( Figure 1B ), adjacent to two conspicuous Ser-Lys tandems ( Loch et al, 2021 ; Loch et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find the optimal zinc concentration for WT ReAV and its mutants, L-asparaginase activity was determined by the Nessler method using the protocol from Loch et al (2023) with 10 mM L-Asn in 20 mM Tris-HCl buffer pH 9.0 and enzyme concentration in the range of 60 nM–3.8 µM, in the presence of zinc ions in concentration varied from 1 to 100 μM (as was the case of the WT and K138A proteins), and additionally extended to the nanomolar range (150–500 nM) in the case of the H139A mutant. The relative activity expressed as the percentage of enzyme activity without zinc supplementation was calculated and plotted to compare the shape of the zinc profiles and the level of response to Zn 2+ .…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of these two proteins show a low level of identity (∼30%) and both are significantly different from the sequences of Class 1 and Class 2 asparaginases ( Loch and Jaskolski, 2021 ). The recently reported crystal structure of ReAIV ( Loch et al, 2023 ) showed that despite the low sequence identity, the two enzymes have basically the same 3D structure.…”
Section: Introductionmentioning
confidence: 99%